Low apoplastic Na+ and intracellular ionic homeostasis confer salinity tolerance upon Ca2SiO4 chemigation in Zea mays L. under salt stress - Mahmood, Moniba Zahid; Odeibat, Hamza Ahmad; Ahmad, Rafiq; Gatasheh, Mansour K.; Shahzad, Muhammad; Abbasi, Arshad Mehmood (Frontiers in Plant Science, 2024)
Salinity is known to have a greater impact on shoot growth than root growth. Na+ buildup in plant tissue under salt stress has been proposed as one of the main issues that causes growth inhibition in crops via ionic imbalances, osmotic stress and pH disturbances. However, the evidence for apoplastic Na+ buildup and the role of silicon in Na+ accumulation at the subcellular level is still enigmatic. The current study focuses on the accumulation of Na+ in the apoplast and symplast of younger and older leaves of two maize varieties (Iqbal as salt-tolerant and Jalal as salt-sensitive) using hydroponic culture along with silicon supplementation under short-term salinity stress. Subcellular ion analysis indicated that silicon nutrition decreased Na+ concentration in both apoplastic washing fluid and symplastic fluid of maize under salt stress. The addition of silicon under NaCl treatment resulted in considerable improvement in fresh biomass, relative water content, chlorophyll content, and concentration of important subcellular ions (i.e., Ca2+, Mg2+, and K+). Knowledge of subcellular ion analysis is essential for solving the mechanisms underlying vital cellular functions e.g. in the current study, the soluble Na+ concentration in the apoplast of older leaves was found to be significantly greater (36.1 mM) in the salt-sensitive variety under NaCl treatment, which was 42.4% higher when compared to the Na+ concentration in the salt-tolerant variety under the same treatment which can influence permeability of cell membrane, signal transduction pathways and provides insights into how ion compartmentalization can contributes to salt tolerance. Calcium silicate enrichment can contribute to increased growth and improved ionic homeostasis by minimizing leaf electrolyte leakage, improving mechanical functions of cell wall and reducing water loss, and improved photosynthetic function. In current investigation, increased water content and intracellular ionic homeostasis along with reduced concentration of Na+ in the maize leaf apoplast suggest that calcium silicate can be used to ameliorate the adverse effects of salt stress and obtain yield using marginal saline lands.